Risk Stratification in Acute Pulmonary Embolism: The Latest Algorithms - Triantafyllou, Georgios A.; O'Corragain, Oisin; Rivera-Lebron, Belinda; Rali, Parth (Seminars in Respiratory and Critical Care Medicine, 2021)
Pulmonary embolism (PE) is a common clinical entity, which most clinicians will encounter. Appropriate risk stratification of patients is key to identify those who may benefit from reperfusion therapy. The first step in risk assessment should be the identification of hemodynamic instability and, if present, urgent patient consideration for systemic thrombolytics. In the absence of shock, there is a plethora of imaging studies, biochemical markers, and clinical scores that can be used to further assess the patients' short-term mortality risk. Integrated prediction models incorporate more information toward an individualized and precise mortality prediction. Additionally, bleeding risk scores should be utilized prior to initiation of anticoagulation and/or reperfusion therapy administration. Here, we review the latest algorithms for a comprehensive risk stratification of the patient with acute PE.
Keywords: pulmonary embolism; risk stratification; prediction tools; algorithms